(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the level of electronic management implementation and its role in enhancing employees’ professional performance at Al-Wehda Bank – Ajilat branch. It also sought to identify statistically significant differences in professional performance attributed to gender and years of experience. The study adopted a descriptive-analytical approach, using a questionnaire as the main data collection tool, distributed to a sample of 60 employees. The results revealed that the level of electronic management implementation was high, and the level of professional performance among employees was also high. The findings indicated statistically significant differences in professional performance based on gender and years of experience, favoring males and more experienced employees. Furthermore, the study found a strong positive statistically significant correlation between electronic management implementation and professional performance. The study recommended enhancing technological infrastructure, strengthening training programs, providing continuous technical support, and adopting incentive policies to promote the use of electronic systems, thereby improving institutional performance in the banking sector.